EKSPLORASI CERITA LOKAL KAMPUNG CILIMUS BERBASIS KAMISHIBAI SEBAGAI SENI PERTUNJUKAN BARU - Rakhman, Rizki Taufik; Leiliyanti, Eva; Prayitno, Eko Hadi; Tesaannisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Cilimus Village, Cisaat Village, Subang, West Java has been declared a Language and Arts Village through the area program under the supervision of Jakarta State University. The Fine ArtsEducation study program responded to this by inviting the English Literature study program to collaborate. The need for new performing arts is the root of the problem in Cilimus village, the aim is to prepare Cilimus village as a Language and Arts village through a new performance that has the uniqueness of Cisaat village, Subang, West Java. This activity is a continuation of the previous year's community services which produced a positive response among the young generation ofCisaat village. The concept of kamishibai originated from Japanese speaking techniques and media which were later adopted into a new performing art. This has been tested in previous activities using participatory experimental methods. However, in this activity the participants consisted of the young generation of Cilimus village aged 15-18 years. Abstrak Kampung Cilimus Desa Cisaat, Subang Jawa Barat telah dicanangkan sebagai kampung Bahasa dan Seni melalui program wilayah binaan Universitas Negeri Jakarta. Program Studi Pendidikan Seni Rupa merespon hal tersebut dengan mengajak prodi Sastra Inggris untuk kolaborasi. Kebutuhan seni pertunjukan baru menjadi akar permasalahan dari kampung Cilimus bertujuan untuk mempersiapkan kampung Cilimus sebagai kampung Bahasa dan Seni melalui sebuah pertunjukan baru yang memiliki kekhas-an desa Cisaat, Subang-Jawa Barat. Kegiatan ini merupakan lanjutan pengabdian pada masyarakat tahun sebelumnya yang menghasilkan respon positif di generasi muda desa Cisaat. Konsep kamishibai bermula dari teknik dan media bertutur di Jepang yang kemudian diadopsi menjadi sebuah seni pertunjukan baru. Hal ini telah diujicobakan dengan menggunakan metode eksperimental partisipatori. Namun, pada kegiatan kali ini para peserta yang terdiri dari generasi muda kampung Cilimus berumur 15-18 tahun.